Tough times for seasoned equity offerings: performance during the COVID pandemic - Marc Zenzius; Christian Flore; Dirk Schiereck (Journal of Business Economics, 2022)
This study analyzes the wealth effects of SEO announcements in the US during the COVID-19 pandemic and its main determinants. We find significantly negative abnormal returns of -0.167em8.6%. This provides persuasive evidence that capital markets reacted particularly negative during this period, reflecting higher degrees of uncertainty. We furthermore find that larger firms experience a better SEO performance and that COVID-19 related biotech & healthcare firms react particularly negative. This effect is more negative the lower the company valuation beforehand.
Keywords: G14; 650; Covid; SEO; Event study